English-Medium Instruction and Content Learning in Higher Education: Effects of Medium of Instruction, English Proficiency, and Academic Ability. (November 2021) - Lin, Teng; Lei, Jun
English-medium instruction (EMI) has become increasingly popular in higher educational institutions across the world due to the prominence of English and the internationalization of higher education. Nevertheless, limited research to date has investigated its impacts on content learning through objective measures. The present study addresses this gap by examining whether students taught in English at a university in China perform differently in a business course from their counterparts taught in Chinese and how English-taught students' English proficiency and academic ability (as measured by grade point average) relate to their EMI academic outcomes. The study employed a quasi-experimental design and adopted inter-translated versions of the same syllabus, textbook, class materials, and exam paper for the English- and Chinese-medium classes. It found no significant differences in students' academic outcomes (i.e., total score, assignment, participation, and final exam) between the English- and the Chinese-taught classes. It also showed that both English proficiency and academic ability were statistically significant predictors of English-taught students' academic outcomes with academic ability being a much stronger predictor than English proficiency. These findings add to a growing but still limited body of evidence on the impacts of EMI on content learning and point to several important implications for EMI.